Corrosion-resistant high-compactness concrete and preparation method thereof
By introducing acrylic emulsion and Kh560 modified fibers into the concrete, combined with the slow release mechanism of corrosion-inhibiting microcapsules, the problem of degradation of traditional concrete in corrosive environments is solved, and high compressive strength and long-term durability are improved.
Patent Information
- Application Number
- CN202510721245.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-08-29
AI Technical Summary
Traditional concrete is susceptible to chloride ions in corrosive environments, resulting in a decrease in durability. The existing materials cannot effectively block chloride ions penetration for a long time, affecting compressive strength and compactness, and it is difficult to meet the long-term use needs in harsh environments.
The corrosion-resistant high-definition concrete formula is adopted, including silicate cement, fly ash, acrylic emulsion, kaolin, quartz stone, quartz sand, dispersant, water reducer, Kh560 modified fiber and corrosion-inhibiting microcapsules. The pores are filled with acrylic emulsion. The Kh560 modified fiber reinforces the strength, and the corrosion-inhibiting microcapsules slowly release corrosion-inhibiting components, combined with the microcapsule wall material to optimize the structure, improve compressive strength and durability.
It improves the anti-chlorine ion penetration properties and long-term durability of concrete, ensures excellent mechanical properties and compressive strength in corrosive environments, and extends service life.
Smart Images

Figure BDA0005429530080000101 
Figure BDA0005429530080000111
Abstract
Description
Technical Field
[0001] The present application belongs to the field of concrete technology, and specifically relates to a corrosion-resistant high-density concrete and a preparation method thereof. Background Art
[0002] Concrete is susceptible to corrosion from harmful media such as chloride ions in corrosive environments, resulting in a decrease in durability. Traditional methods improve corrosion resistance by incorporating fly ash, air-entraining agents, or expansion agents. However, these materials often fail to effectively block chloride ion penetration over the long term, affecting the density of concrete and thus reducing its compressive strength. Over time, the anti-corrosion effect gradually weakens, making it difficult to meet the requirements of long-term use in harsh environments. Therefore, there is an urgent need to develop a new type of concrete that combines high corrosion resistance with good mechanical properties to improve structural durability and extend service life. Summary of the Invention
[0003] In view of this, the present application provides a concrete with good corrosion resistance and compressive strength.
[0004] In a first aspect, the present application provides a corrosion-resistant high-density concrete, which comprises the following raw materials in parts by weight: 500-600 parts of Portland cement, 47-53 parts of fly ash, 10-20 parts of acrylic emulsion, 50-80 parts of kaolin, 1260-1400 parts of quartz stone, 830-920 parts of quartz sand, 0.5-1 part of dispersant, 9-13 parts of water reducer, 180-200 parts of water, 20-40 parts of Kh560 modified fiber, and 20-40 parts of corrosion-inhibiting microcapsules; The corrosion-inhibiting microcapsule comprises a core material and a wall material covering the core material; The core material includes dimethylethanolamine and sodium monofluorophosphate in a weight ratio of 1:(3-5); The wall material includes sodium fatty alcohol polyoxyethylene ether sulfate and polyvinyl alcohol in a weight ratio of (2.5-3.5):1; The weight ratio of the core material to the wall material is 1:(1.5-2.5).
[0005] By adopting the above technical solution, the corrosion-resistant high-density concrete provided by this application has better resistance to chloride ion penetration and long-term durability. Among them, the acrylic emulsion fills the pores inside the concrete, improves the density, and at the same time, together with the Kh560 modified fiber, enhances the overall strength and adhesion of the concrete. The corrosion-inhibiting microcapsules contain dimethylethanolamine and sodium monofluorophosphate. The combined use of dimethylethanolamine and sodium monofluorophosphate can be slowly released into the concrete during the use of the concrete, continuously preventing the corrosion of chloride ions; and the wall material of the microcapsule is composed of fatty alcohol polyoxyethylene ether sodium sulfate and polyvinyl alcohol, ensuring that the core material components can be released stably and in a timely manner. In addition, the corrosion-inhibiting microcapsules can fill the gaps in the concrete, and when used in combination with the Kh560 modified fiber, further improve the compressive strength of the concrete. The addition of kaolin further optimizes the structure of the concrete, reduces harmful pores, and enhances the compressive strength of the concrete. Therefore, the concrete provided by this application not only has a high initial compressive strength, but also can maintain excellent mechanical properties and durability in a long-term corrosive environment.
[0006] In some embodiments, the Kh560 modified fiber is obtained by modifying Kh560; the fiber comprises basalt fiber and seaweed fiber in a weight ratio of 1:1.
[0007] By adopting the above technical solution, the compressive strength of concrete can be improved by using basalt fiber and seaweed fiber in the above ratio in the present application.
[0008] In some embodiments, the core material includes dimethylethanolamine and sodium monofluorophosphate in a weight ratio of 1:4.2.
[0009] By adopting the above technical solution, the weight ratio of dimethylethanolamine and sodium monofluorophosphate in the core material is controlled within the above appropriate range, which can further improve the compressive strength and corrosion resistance of concrete.
[0010] In some embodiments, the weight ratio of Kh560 modified fiber to corrosion-inhibiting microcapsules is 1:(0.8-1.2).
[0011] By adopting the above technical solution, the weight ratio of Kh560 modified fiber and corrosion-inhibiting microcapsules is controlled within the above appropriate range, which can further improve the compressive strength and corrosion resistance of concrete.
[0012] In some embodiments, the weight ratio of the Kh560 modified fiber to the corrosion-inhibiting microcapsules is 1:1.
[0013] By adopting the above technical solution, the weight ratio of Kh560 modified fiber and corrosion-inhibiting microcapsules is controlled within the above appropriate range, which can further improve the compressive strength and corrosion resistance of concrete.
[0014] In some embodiments, the dispersant includes sodium hexametaphosphate.
[0015] In some embodiments, the method for preparing the corrosion-inhibiting microcapsules comprises the following steps: A1. The core material is prepared into a 20-30 wt% aqueous solution, and the wall material is prepared into a 10-15 wt% aqueous solution; A2. Add the core material solution to the wall material solution and emulsify at 7000-9000 rpm for 8-12 minutes; A3. Add the emulsion dropwise to mineral oil containing 2-3 wt% Span-80, react at 40±2° C. for 1.5-2.5 hours, filter, wash, and dry to obtain the corrosion-inhibiting microcapsules.
[0016] By adopting the above technical solution and the above preparation method, the present application ensures that the corrosion-inhibiting microcapsules have good stability and controlled release properties, enabling them to effectively and slowly release the corrosion-inhibiting ingredients during the service life of concrete, continuously inhibiting chloride ion corrosion, thereby enhancing the corrosion resistance and long-term durability of the concrete. The synergistic effect of these corrosion-inhibiting microcapsules and Kh560 modified fiber further enhances the overall compressive strength and corrosion resistance of the concrete.
[0017] In some embodiments, the water reducer is selected from polycarboxylate water reducers.
[0018] In some embodiments, the basalt fiber has a diameter of 13-15 μm and a length of 12-18 mm; the seaweed fiber has a diameter of 20-25 μm and a length of 6-10 mm. By adopting the above technical solution, the fiber length and diameter are controlled within the above ranges, which can maintain good compressive strength and corrosion resistance for concrete.
[0019] In a second aspect, the present application provides a method for preparing corrosion-resistant high-density concrete, the preparation method comprising the following steps: S1. Mixing and stirring Portland cement, fly ash, kaolin, quartz sand, quartz stone, and a dispersant to prepare a first mixture; S2, adding acrylic emulsion, water reducer and water to the first mixture, stirring to form a slurry; S3, adding KH560 modified fiber and corrosion-inhibiting microcapsules to the slurry, stirring evenly to prepare a second mixture; S4. Pour the second mixed material into a standard mold, vibrate and compact it, and naturally cure it after molding to obtain the corrosion-resistant high-density concrete.
[0020] By adopting the above-mentioned technical solution, the preparation method provided in this application can not only effectively improve the compressive strength of concrete, but also ensure the uniform distribution of corrosion-inhibiting microcapsules and modified fibers in the concrete structure, thereby providing continuous anti-corrosion protection and enhancement effects during long-term use, and is suitable for engineering environments with high requirements for corrosion resistance.
[0021] In summary, the present invention includes at least one of the following beneficial technical effects: The corrosion-resistant high-density concrete provided by the present application has excellent resistance to chloride ion penetration and long-term durability. Among them, the acrylic emulsion fills the pores inside the concrete, improves the density, and at the same time, together with the Kh560 modified fiber, enhances the overall strength and adhesion of the concrete. The corrosion-inhibiting microcapsules contain dimethylethanolamine and sodium monofluorophosphate. The compound use of dimethylethanolamine and sodium monofluorophosphate can be slowly released into the concrete during the use of the concrete, continuously preventing the corrosion of chloride ions; and the wall material of the microcapsule is composed of fatty alcohol polyoxyethylene ether sodium sulfate and polyvinyl alcohol, ensuring that the core material components can be released stably and timely. In addition, the corrosion-inhibiting microcapsules can fill the gaps in the concrete, and when used in combination with the Kh560 modified fiber, further improve the compressive strength of the concrete. The addition of kaolin further optimizes the structure of the concrete, reduces harmful pores, and enhances the compressive strength of the concrete. Therefore, the concrete provided by the present application not only has a high initial compressive strength, but also can maintain excellent mechanical properties and durability in a long-term corrosive environment. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of this application more clear, the following further describes this application in detail with reference to the embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not intended to limit this application.
[0023] Concrete is susceptible to corrosion by harmful media such as chloride ions in a corrosive environment, resulting in a decrease in durability. Traditional methods improve corrosion resistance by adding fly ash, air-entraining agents or expansion agents, but these materials are often unable to effectively block chloride ion penetration in the long term, which not only affects the density of concrete, but also reduces the compressive strength of concrete. As time goes by, the anti-corrosion effect gradually weakens, making it difficult to meet the long-term use requirements in harsh environments. Therefore, there is an urgent need to develop a new type of concrete that has both high corrosion resistance and good mechanical properties to improve structural durability and extend service life. In view of this, the inventors of this application have provided a concrete with better corrosion resistance, higher density and better compressive strength through research. In a first aspect, the present application provides a corrosion-resistant high-density concrete, which comprises the following raw materials in parts by weight: 500-600 parts of Portland cement, 47-53 parts of fly ash, 10-20 parts of acrylic emulsion, 50-80 parts of kaolin, 1260-1400 parts of quartz stone, 830-920 parts of quartz sand, 0.5-1 part of dispersant, 9-13 parts of water reducer, 180-200 parts of water, 20-40 parts of Kh560 modified fiber, and 20-40 parts of corrosion-inhibiting microcapsules; The corrosion-inhibiting microcapsule comprises a core material and a wall material covering the core material; The core material includes dimethylethanolamine and sodium monofluorophosphate in a weight ratio of 1:(3-5); The wall material includes sodium fatty alcohol polyoxyethylene ether sulfate and polyvinyl alcohol in a weight ratio of (2.5-3.5):1; The weight ratio of the core material to the wall material is 1:(1.5-2.5). By adopting the above technical solution, the corrosion-resistant high-density concrete provided by the present application has better resistance to chloride ion penetration and long-term durability. Among them, the acrylic emulsion fills the pores inside the concrete, improves the density, and at the same time, together with the Kh560 modified fiber, enhances the overall strength and adhesion of the concrete. The corrosion-inhibiting microcapsules contain dimethylethanolamine and sodium monofluorophosphate. The compound use of dimethylethanolamine and sodium monofluorophosphate can be slowly released into the concrete during the use of the concrete, continuously preventing the corrosion of chloride ions; and the wall material of the microcapsule is composed of fatty alcohol polyoxyethylene ether sodium sulfate and polyvinyl alcohol, which ensures that the core material components can be released stably and timely. In addition, the corrosion-inhibiting microcapsules can fill the voids in the concrete, and when used in combination with the Kh560 modified fiber, the compressive strength of the concrete is further improved. The addition of kaolin further optimizes the structure of the concrete, reduces harmful pores, and enhances the compressive strength of the concrete. Therefore, the concrete provided by the present application not only has high initial compressive strength, but also can maintain excellent mechanical properties and durability in a long-term corrosive environment.
[0024] In some embodiments, Kh560 modified fiber is produced by modifying Kh560 fibers; the fibers include basalt fiber and seaweed fiber in a weight ratio of 1:1. By adopting the above technical solution, the compressive strength of concrete can be improved by using the above ratio of basalt fiber and seaweed fiber in this application.
[0025] In some embodiments, the core material includes dimethylethanolamine and sodium monofluorophosphate in a weight ratio of 1:4.2. By adopting the above technical solution, the weight ratio of dimethylethanolamine to sodium monofluorophosphate in the core material is controlled within the above suitable range, which can further improve the compressive strength and corrosion resistance of the concrete.
[0026] In some embodiments, the weight ratio of Kh560 modified fiber to corrosion-inhibiting microcapsules is 1:(0.8-1.2). By adopting the above technical solution and regulating the weight ratio of Kh560 modified fiber to corrosion-inhibiting microcapsules within the above appropriate range, the compressive strength and corrosion resistance of concrete can be further improved.
[0027] In some embodiments, the weight ratio of Kh560 modified fiber to the corrosion-inhibiting microcapsules is 1: 1. By adopting the above technical solution and regulating the weight ratio of Kh560 modified fiber to corrosion-inhibiting microcapsules within the above appropriate range, the compressive strength and corrosion resistance of concrete can be further improved.
[0028] In some embodiments, the dispersant includes sodium hexametaphosphate.
[0029] In some embodiments, the method for preparing the corrosion-inhibiting microcapsules comprises the following steps: A1. The core material is prepared into a 20-30 wt% aqueous solution, and the wall material is prepared into a 10-15 wt% aqueous solution; A2. Add the core material solution to the wall material solution and emulsify at 7000-9000 rpm for 8-12 minutes; A3. Add the emulsion dropwise to mineral oil containing 2-3wt% Span-80, react at 40±2°C for 1.5-2.5 hours, filter, wash, and dry to produce the corrosion-inhibiting microcapsules. By adopting the above technical solution, the present application and the preparation method can ensure that the corrosion-inhibiting microcapsules have good stability and controlled release properties, enabling them to effectively and slowly release the corrosion-inhibiting ingredients during the service life of concrete, continuously inhibiting chloride ion corrosion, thereby enhancing the corrosion resistance and long-term durability of the concrete. The combined effect of these corrosion-inhibiting microcapsules and Kh560 modified fibers further enhances the overall compressive strength and corrosion resistance of the concrete.
[0030] In some embodiments, the water reducer is selected from polycarboxylate water reducers.
[0031] In some embodiments, the basalt fiber has a diameter of 13-15 μm and a length of 12-18 mm; the seaweed fiber has a diameter of 20-25 μm and a length of 6-10 mm. By adopting the above technical solution, the fiber length and diameter are controlled within the above ranges, which can maintain good compressive strength and corrosion resistance for concrete.
[0032] In a second aspect, the present application provides a method for preparing corrosion-resistant high-density concrete, the preparation method comprising the following steps: S1. Mixing and stirring Portland cement, fly ash, kaolin, quartz sand, quartz stone, and a dispersant to prepare a first mixture; S2, adding acrylic emulsion, water reducer and water to the first mixture, stirring to form a slurry; S3, adding KH560 modified fiber and corrosion-inhibiting microcapsules to the slurry, stirring evenly to prepare a second mixture; S4. Pour the second mixture into a standard mold, oscillate and compact it, and then naturally cure it after forming to obtain the corrosion-resistant, high-density concrete. By adopting the above technical solution, the preparation method provided in this application can not only effectively improve the compressive strength of concrete, but also ensure the uniform distribution of corrosion-inhibiting microcapsules and modified fibers in the concrete structure, thereby providing continuous anti-corrosion protection and reinforcement effects during long-term use, and is suitable for engineering environments with high corrosion resistance requirements.
[0033] The scheme of the present application is described below with reference to the following specific examples. Unless otherwise specified, the raw materials used in the following examples are all from common commercial products, and the devices or equipment used are all purchased from conventional market sales channels.
[0034] Preparation Example 1 to Preparation Example 3 Preparation Example 1 This preparation example provides a corrosion-inhibiting microcapsule, which includes a core material and a wall material coated outside the core material; the core material includes dimethylethanolamine and sodium monofluorophosphate in a weight ratio of 1:3; The wall material includes sodium fatty alcohol polyoxyethylene ether sulfate and polyvinyl alcohol in a weight ratio of 2.5:1; The weight ratio of core material to wall material is 1:1.5.
[0035] The preparation method of corrosion-inhibiting microcapsules comprises the following steps: A1. Prepare the core material into a 20 wt% aqueous solution and the wall material into a 10 wt% aqueous solution; A2. Add the core material solution to the wall material solution and emulsify at 7000 rpm for 8 minutes; A3. Add the emulsion dropwise to mineral oil containing 2 wt% Span-80, react at 40±2°C for 1.5 hours, filter, wash (wash 3 times with petroleum ether), and dry (dry at 40°C for 4 hours) to obtain corrosion-inhibiting microcapsules.
[0036] Preparation Example 2 This preparation example provides a corrosion-inhibiting microcapsule, which includes a core material and a wall material coated outside the core material; the core material includes dimethylethanolamine and sodium monofluorophosphate in a weight ratio of 1:4.2; The wall material includes sodium sulfate of fatty alcohol polyoxyethylene ether and polyvinyl alcohol in a weight ratio of 3:1; The weight ratio of core material to wall material is 1:2.
[0037] The preparation method of corrosion-inhibiting microcapsules comprises the following steps: A1. Prepare the core material into a 25 wt% aqueous solution and the wall material into a 13 wt% aqueous solution; A2. Add the core material solution to the wall material solution and emulsify at 8000 rpm for 10 minutes; A3. Add the emulsion dropwise into mineral oil containing 2.5 wt% Span-80, react at 40±2°C for 2 hours, filter, wash and dry to obtain corrosion-inhibiting microcapsules.
[0038] Preparation Example 3 This preparation example provides a corrosion-inhibiting microcapsule, which includes a core material and a wall material coated outside the core material; the core material includes dimethylethanolamine and sodium monofluorophosphate in a weight ratio of 1:5; The wall material includes sodium fatty alcohol polyoxyethylene ether sulfate and polyvinyl alcohol in a weight ratio of 3.5:1; The weight ratio of core material to wall material is 1:2.5.
[0039] The preparation method of corrosion-inhibiting microcapsules comprises the following steps: A1. Prepare the core material into a 30 wt% aqueous solution and the wall material into a 15 wt% aqueous solution; A2. Add the core material solution to the wall material solution and emulsify at 9000 rpm for 12 minutes; A3. Add the emulsion dropwise into mineral oil containing 3 wt% Span-80, react at 40±2°C for 2.5 hours, filter, wash and dry to obtain corrosion-inhibiting microcapsules.
[0040] Example 1 to Example 4 Example 1 This embodiment provides a corrosion-resistant high-density concrete, which includes the following raw materials in parts by weight: 500 parts of Portland cement, 47 parts of fly ash, 10 parts of acrylic emulsion, 50 parts of kaolin, 1260 parts of quartz stone, 830 parts of quartz sand, 0.5 parts of dispersant, 9 parts of water reducer, 180 parts of water, 35 parts of Kh560 modified fiber, and 35 parts of corrosion-inhibiting microcapsules; The preparation method comprises the following steps: S1. Mixing and stirring Portland cement, fly ash, kaolin, quartz sand, quartz stone, and a dispersant to prepare a first mixture; S2, adding acrylic emulsion, water reducer and water to the first mixture, stirring to form a slurry; S3, adding KH560 modified fiber and corrosion-inhibiting microcapsules to the slurry, stirring evenly to prepare a second mixture; S4. Pour the second mixture into a standard mold, vibrate and compact it, and then naturally cure it after molding to obtain corrosion-resistant high-density concrete.
[0041] The silicate cement used in this embodiment is P.O42.5 ordinary silicate cement.
[0042] The fly ash used in this embodiment is Class I ash.
[0043] The dispersant used in this embodiment is sodium hexametaphosphate.
[0044] The water reducer in this embodiment is a polycarboxylate water reducer.
[0045] Kh560 modified fiber is made by modifying Kh560 fibers. The fibers consist of basalt fiber and seaweed fiber in a weight ratio of 1:1. The basalt fiber has a diameter of 13-15μm and a length of 12-18mm, while the seaweed fiber has a diameter of 20-25μm and a length of 6-10mm.
[0046] The preparation method of KH560 modified fiber includes the following steps: first, basalt fiber and seaweed fiber mixed in a weight ratio of 1:1 are placed in a 60°C ethanol solution for ultrasonic cleaning to remove surface impurities, and then dried for standby use; then, KH560 silane coupling agent is dissolved in an ethanol-water mixed solution (the volume ratio of ethanol to water is 9:1) to prepare a modification solution with a mass fraction of 3%, the pH is adjusted to 5 with acetic acid and hydrolyzed, and the pretreated fiber is immersed in the modification solution and stirred at a constant temperature of 60°C to fully graft siloxane groups on the fiber surface; then, the fiber is taken out, dried and solidified, and cooled to room temperature to obtain the KH560 modified fiber finished product.
[0047] Example 2 to Example 4 Example 2 The difference between this embodiment and embodiment 1 is that, in this embodiment, when preparing corrosion-resistant high-density concrete, the total weight of Kh560 modified fiber and corrosion-inhibiting microcapsules is 70 parts, wherein the weight ratio of Kh560 modified fiber to corrosion-inhibiting microcapsules is 1:0.8.
[0048] Example 3 The difference between this embodiment and embodiment 1 is that, in this embodiment, when preparing corrosion-resistant high-density concrete, the total weight of Kh560 modified fiber and corrosion-inhibiting microcapsules is 70 parts, wherein the weight ratio of Kh560 modified fiber to corrosion-inhibiting microcapsules is 1:1.1.
[0049] Example 4 The difference between this embodiment and embodiment 1 is that, in this embodiment, when preparing corrosion-resistant high-density concrete, the total weight of Kh560 modified fiber and corrosion-inhibiting microcapsules is 70 parts, wherein the weight ratio of Kh560 modified fiber to corrosion-inhibiting microcapsules is 1:1.2.
[0050] Comparative Example 1 The difference between this embodiment and embodiment 1 is that Kh560 modified fiber is not added when preparing the corrosion-resistant high-density concrete.
[0051] Comparative Example 2 The difference between this embodiment and embodiment 1 is that no corrosion-inhibiting microcapsules are added when preparing the corrosion-resistant high-density concrete.
[0052] Comparative Example 3 The difference between this embodiment and embodiment 1 is that, when preparing the corrosion-resistant high-density concrete, no corrosion-inhibiting microcapsules and Kh560 modified fibers were added.
[0053] Experimental testing: Compressive strength: Tested in accordance with the cube specimen method (150mm×150mm×150mm) "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T50081-2019).
[0054] Corrosion resistance coefficient: GB / T50082-2009 (sulfate attack). (Strength retention after 56 days of immersion).
[0055] Table 1 - Experimental test results of Examples 1-4 and Comparative Examples 1-6 Example Compressive strength (28d, Mpa) 56d compressive strength retention rate (%) Example 1 81.3 93.27 Example 2 79.8 90.15 Example 3 80.7 92.39 Example 4 80.2 91.64 Comparative Example 1 68.5 84.39 Comparative Example 2 74.2 82.06 Comparative Example 3 62.7 75.33 Results: Analysis of the performance of concrete with different mix ratios reveals that concrete incorporating KH560 modified fibers and corrosion-inhibiting microcapsules exhibits significant advantages in both mechanical properties and corrosion resistance. The sample with a 1:1 fiber to microcapsule ratio performed the best, achieving an optimal balance between compressive strength and sulfate resistance. In contrast, the control group, without either fiber or microcapsules, exhibited a significant performance decline, with the sample lacking both components showing the most pronounced performance degradation.
[0056] Examples 5-6 The difference between Example 5-6 and Example 1 is that, when preparing the corrosion-resistant high-density concrete, the weight percentages of some components are different. The differences are shown in Table 2.
[0057] Table 2 - Differences between Examples 5-6 and Example 2 Element Example 1 Example 5 Example 6 Portland cement 500 570 600 fly ash 47 50 53 Acrylic emulsion 10 15 20 Kaolin 50 70 80 Quartz 1260 1355 1400 quartz sand 830 895 920 dispersants 0.5 0.8 1 water reducer 9 11 13 water 180 190 200 Kh560 modified fiber 35 35 35 Corrosion inhibition microcapsules 35 35 35 The experimental test results of Examples 5-6 are shown in Table 3.
[0058] Table 3 - Experimental test results of Examples 5-6 Example Compressive strength (28d, Mpa) 56d compressive strength retention rate (%) Example 1 81.3 93.27 Example 5 83.5 94.85 Example 6 82.4 93.92 Result analysis: The difference between Example 5-6 and Example 1 is that when preparing the corrosion-resistant high-density concrete, the weight proportions of some components are different. Combined with the experimental test results in Table 3, it can be seen that the comprehensive performance of the corrosion-resistant high-density concrete prepared by Example 5 is better.
[0059] Example 7 The difference between Examples 7-11 and Example 5 is that when preparing corrosion-resistant high-density concrete, on the premise that the weight ratio of Kh560 modified fiber and corrosion-inhibiting microcapsules is 1:1, the total weight ratio of Kh560 modified fiber and corrosion-inhibiting microcapsules in the corrosion-resistant high-density concrete is changed, and a better weight ratio is selected.
[0060] In Example 5, the total weight of Kh560 modified fiber and corrosion-inhibiting microcapsules is 70 parts, and the total weight of corrosion-resistant high-density concrete is 3226.8 parts.
[0061] Therefore, it is not difficult to conclude that in Example 5, the proportion of Kh560 modified fiber (called variable 1) and corrosion-inhibiting microcapsules (called variable 2) in the corrosion-resistant high-density concrete (called matrix) is 2.17%.
[0062] The differences between Examples 7-11 and Example 5 are shown in Table 4.
[0063] Proportion = (variable 1 + variable 2) / total weight of matrix * 100%.
[0064] Table 4 - Differences between Examples 7-11 and Example 5 The experimental test results of Examples 7-11 are shown in Table 5.
[0065] Table 5 - Experimental test results of Examples 7-11 Example Compressive strength (28d, Mpa) 56d compressive strength retention rate (%) Example 5 83.5 94.85 Example 7 80.6 91.50 Example 8 81.3 92.37 Example 9 81.7 92.84 Example 10 82.9 93.98 Example 11 82.4 93.52 Results analysis: The difference between Examples 7-11 and Example 5 is that, when preparing corrosion-resistant high-density concrete, the total weight ratio of Kh560 modified fiber and corrosion-inhibiting microcapsules in the corrosion-resistant high-density concrete is different. Combined with the experimental test results in Table 5, it can be seen that when the total weight ratio of Kh560 modified fiber and corrosion-inhibiting microcapsules in the corrosion-resistant high-density concrete is 1.5% to 2.5%, the comprehensive performance of the corrosion-resistant high-density concrete is better. When the total weight ratio of Kh560 modified fiber and corrosion-inhibiting microcapsules in the corrosion-resistant high-density concrete is 2.17%, the comprehensive performance of the corrosion-resistant high-density concrete is the best. When the ratio is too high or too low, the comprehensive performance is reduced.
[0066] Examples 12-13 Example 12 The difference between this embodiment and embodiment 5 is that different preparation parameters of the corrosion-inhibiting microcapsules are used in preparing corrosion-resistant high-density concrete. The corrosion-inhibiting microcapsules in this embodiment are prepared by Preparation Example 2.
[0067] Example 13 The difference between this example and Example 5 is that different preparation parameters of the corrosion-inhibiting microcapsules used in preparing corrosion-resistant high-density concrete are used. The corrosion-inhibiting microcapsules in this example are prepared according to Preparation Example 3. The experimental test results of Examples 12-13 are shown in Table 6.
[0068] Table 6 - Experimental test results of Examples 12-13 Results Analysis: The difference between Examples 12-13 and Example 5 is that different preparation parameters of the corrosion-inhibiting microcapsules were used in preparing corrosion-resistant, high-density concrete. Combined with the experimental test results in Table 6, it can be seen that the corrosion-resistant, high-density concrete prepared in Example 12 has better overall performance.
[0069] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the principles of the present application should be included in the scope of protection of the present application.
Claims
1. A corrosion-resistant high-density concrete, characterized in that: The concrete comprises the following raw materials in parts by weight: 500-600 parts of Portland cement, 47-53 parts of fly ash, 10-20 parts of acrylic emulsion, 50-80 parts of kaolin, 1260-1400 parts of quartz stone, 830-920 parts of quartz sand, 0.5-1 part of dispersant, 9-13 parts of water reducer, 180-200 parts of water, 20-40 parts of Kh560 modified fiber, and 20-40 parts of corrosion inhibition microcapsules; The corrosion-inhibiting microcapsule comprises a core material and a wall material coated on the outside of the core material; The core material comprises dimethylethanolamine and sodium monofluorophosphate in a weight ratio of 1:(3-5); The wall material comprises sodium fatty alcohol polyoxyethylene ether sulfate and polyvinyl alcohol in a weight ratio of (2.5-3.5):1; The weight ratio of the core material to the wall material is 1:(1.5-2.5).
2. The corrosion-resistant high-density concrete according to claim 1, characterized in that: The Kh560 modified fiber is prepared by modifying Kh560 fiber; the fiber comprises basalt fiber and seaweed fiber in a weight ratio of 1:
1.
3. The corrosion-resistant high-density concrete according to claim 1, characterized in that: The core material comprises dimethylethanolamine and sodium monofluorophosphate in a weight ratio of 1:4.
2.
4. The corrosion-resistant high-density concrete according to claim 1, characterized in that: The weight ratio of the Kh560 modified fiber to the corrosion-inhibiting microcapsule is 1:(0.8-1.2).
5. The corrosion-resistant high-density concrete according to claim 4, characterized in that: The weight ratio of the Kh560 modified fiber to the corrosion-inhibiting microcapsule is 1:
1.
6. The corrosion-resistant high-density concrete according to claim 1, characterized in that: The dispersant includes sodium hexametaphosphate.
7. The corrosion-resistant high-density concrete according to claim 1, characterized in that: The preparation method of the corrosion-inhibiting microcapsules comprises the following steps: A1. The core material is prepared into a 20-30 wt% aqueous solution, and the wall material is prepared into a 10-15 wt% aqueous solution; A2. Add the core material solution to the wall material solution and emulsify at 7000-9000 rpm for 8-12 minutes; A3. Add the emulsion dropwise to mineral oil containing 2-3 wt% Span-80, react at 40±2° C. for 1.5-2.5 hours, filter, wash, and dry to obtain the corrosion-inhibiting microcapsules.
8. The corrosion-resistant high-density concrete according to claim 1, characterized in that: The water reducer is selected from polycarboxylate water reducer.
9. The corrosion-resistant high-density concrete according to claim 1, characterized in that: The basalt fiber has a diameter of 13-15 μm and a length of 12-18 mm; the seaweed fiber has a diameter of 20-25 μm and a length of 6-10 mm.
10. A method for preparing the corrosion-resistant high-density concrete according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: S1. Mixing and stirring Portland cement, fly ash, kaolin, quartz sand, quartz stone, and a dispersant to prepare a first mixture; S2, adding acrylic emulsion, water reducer and water to the first mixture, stirring to form a slurry; S3, adding KH560 modified fiber and corrosion-inhibiting microcapsules to the slurry, stirring evenly to prepare a second mixture; S4. Pour the second mixed material into a standard mold, vibrate and compact it, and naturally cure it after molding to obtain the corrosion-resistant high-density concrete.
Citation Information
Patent Citations
Chemical trigger microcapsule and preparation method thereof
CN103962072A
Corrosion inhibitor slow-release microcapsule and preparation method thereof
CN106380111A
Construction method of cast-in-situ bored pile
CN110093915A
Environmental complex response homogeneous expansion type self-repairing microcapsule for concrete, and preparation method thereof
CN113735485A
Environment-friendly pervious concrete and preparation method thereof
CN117550849A
